2009
DOI: 10.1021/jp808790j
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Electronic Transport in Double-Stranded DNA Nucleotides

Abstract: We calculate the transverse current through double-stranded DNA nucleotides using ab initio techniques in order to establish a protocol to recognize the type and sequence of double-stranded DNA nucleotides. The distinct current-voltage features between nucleotides are used as signatures for their characterization and sequencing. Extended bulk gold electrodes as well as extensions of the DNA backbones are tested as contacts for the electron transport, yielding currents 2 orders of magnitude larger for the forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 61 publications
3
22
0
1
Order By: Relevance
“…This result confirms the study by Jauregui and coworkers that the ds DNAs ͑A-T͒ and ͑C-G͒ exhibit different electronic characteristics due to their different density of states. 17 The Fermi levels associated with the four bases, ds DNAs ͑A-T͒ and …”
Section: Methodsmentioning
confidence: 99%
“…This result confirms the study by Jauregui and coworkers that the ds DNAs ͑A-T͒ and ͑C-G͒ exhibit different electronic characteristics due to their different density of states. 17 The Fermi levels associated with the four bases, ds DNAs ͑A-T͒ and …”
Section: Methodsmentioning
confidence: 99%
“…Nosotros aplicamos estas técnicas para predecir las características electrónicas de un sistema, el cual puede ser el mismo fenómeno a detectar, como la secuencia de nucleótidos erradas en el DNA; así como moléculas e interfaces de los componentes electrónicos del nano-sensor. Para la lectura de secuencias de nucleótidos, nuestras investigaciones concluyen que las características eléctricas son identificables durante la medición transversal de la corriente, simulando el paso vertical y controlado del DNA dentro de un poro con nano-electrodos de oro en su interior [32,33]. Errores de complementariedad de los nucleótidos como AA, CC, GG, TT resultan menos conductivos que los pares complementarios de nucleótidos, siendo el más conductor el par CT [33].…”
Section: Transporte De Electronesunclassified
“…In Ref. , they calculated the transverse current through double‐stranded DNA nucleotide and showed that the current–voltage features provide signatures for DNA sequencing. Also electron‐tunneling properties of different base pairs (G‐C, A‐T, G‐T, and 2AA‐T) have been investigated by Lee and Sankey .…”
Section: Introductionmentioning
confidence: 99%